Предмет:
МатематикаАвтор:
анонимНайдем значение выражения:
(-2) * (+1/4) * (-3/5) * (-4/3)/(19,2 + (-11,2) - 7) = -2 * 1/4 * (-3/5) * (-4/3)/(19,2 -11,2 - 7) = -2 * 1/4 * 3/5 * 4/3/(19,2 - 18,2) = -1 * 1/2 * 3/5 * 4/3/(19,2 - 18,2) = -1/2 * (1/5 * 4/1)/(19,2 - 18,2) = -1/2 * 4/5/(19,2 - 18,2) = -1/1 * 2/5/(19,2 - 18,2) = -2/5/(19,2 - 18,2) = -0,4/(19,2 - 18,2) = -4/(19,2 - 18,2) = -4/1 = -4;
В итоге получили, (-2) * (+1/4) * (-3/5) * (-4/3)/(19,2 + (-11,2) - 7) = -4.
Автор:
twixdcfeДобавить свой ответ
Предмет:
БиологияАвтор:
aussierobertsОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть